A furosemide-sensitive K+-Cl−cotransporter counteracts intracellular Cl− accumulation and depletion in cultured rat midbrain neurons - Jarolimek, Wolfgang; Lewen, Andrea; Misgeld, Ulrich (The journal of neuroscience, 1999)
Efficacy of postsynaptic inhibition through GABAAreceptors in the mammalian brain depends on the maintenance of a Cl− gradient for hyperpolarizing Cl− currents. We have taken advantage of the reduced complexity under which Cl− regulation can be investigated in cultured neurons as opposed to neurons in otherin vitro preparations of the mammalian brain. Tightseal whole-cell recording of spontaneous GABAAreceptor-mediated postsynaptic currents suggested that an outward Cl− transport reduced dendritic [Cl−]i if the somata of cells were loaded with Cl− via the patch pipette. We determined dendritic and somatic reversal potentials of Cl− currents induced by focally applied GABA to calculate [Cl−]i during variation of [K+]o and [Cl−] in the patch pipette. [Cl−]i and [K+]o were tightly coupled by a furosemide-sensitive K+-Cl−cotransport. Thermodynamic considerations excluded the significant contribution of a Na+-K+-Cl−cotransporter to the net Cl− transport. We conclude that under conditions of normal [K+]othe K+-Cl− cotransporter helps to maintain [Cl−]i at low levels, whereas under pathological conditions, under which [K+]o remains elevated because of neuronal hyperactivity, the cotransporter accumulates Cl− in neurons, thereby further enhancing neuronal excitability.
Im Text sind "+" und "-" hochgestellt
Gesehen am 27.04.2021